Correlates of STI testing among vocational school students in the Netherlands - Mackenbach Johan P; Kok Gerjo; Wolfers Mireille EG; de Zwart Onno (BMC, 2010)
Abstract Background Adolescents are at risk for acquiring sexually transmitted infections (STIs). However, test rates among adolescents in the Netherlands are low and effective interventions that encourage STI testing are scarce. Adolescents who attend vocational schools are particularly at risk for STI. The purpose of this study is to inform the development of motivational health promotion messages by identifying the psychosocial correlates of STI testing intention among adolescents with sexual experience attending vocational schools. Methods This study was conducted among 501 students attending vocational schools aged 16 to 25 years (mean 18.3 years ± 2.1). Data were collected via a web-based survey exploring relationships, sexual behavior and STI testing behavior. Items measuring the psychosocial correlates of testing were derived from Fishbein's Integrative Model. Data were subjected to multiple regression analyses. Results Students reported substantial sexual risk behavior and low intention to participate in STI testing. The model explained 39% of intention to engage in STI testing. The most important predictor was attitude. Perceived norms, perceived susceptibility and test site characteristics were also significant predictors. Conclusions The present study provides important and relevant empirical input for the development of health promotion interventions aimed at motivating adolescents at vocational schools in the Netherlands to participate in STI testing. Health promotion interventions developed for this group should aim to change attitudes, address social norms and increase personal risk perception for STI while also promoting the accessibility of testing facilities.